Optical Imaging of Cancer Clinical Applications - Rosenthal, Eben.; Zinn, Kurt R.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Optical detection represents the next great horizon for cancer imaging. As molecularly targeted therapeutic agents are delivered to the clinic in increasing numbers, there is a parallel opportunity to advance optical imaging techniques. Because of its limited toxicity and potential for real-time information, optical imaging represents an underdeveloped modality in clinical medicine. Optical Imaging of Cancer: Clinical Applications explores the preclinical and clinical data to support the use of these techniques in cancer imaging. Different fluorescent delivery modalities are explored: from monoclonal antibodies to viral vector delivery. Indications for use include monitoring therapuetic delivery, early detection, and operative removal techniques in all stages of clinical development. This book represents the best and most clinically relevant techniques currently available.
I: Optical Imaging Principles -- Optical Imaging of Cancer: Enhancing Detection and Resection -- Endoscopic Techniques for Optical Imaging -- Design and Use of the Surgical Microscope in Fluorescence-Guided Surgery -- Fluorophores for Optical Imaging -- II: Cancer Targeting Strategies -- Overview of Cancer Detection and Monitoring Strategies -- The Application of Tissue Autofluorescence in Detection and Management of Oral Cancer and Premalignant Lesions -- Proteinase Optical Imaging Tools for Cancer Detection and Response to Therapy -- Illustrating Molecular Events with Light: A Perspective on Optical Reporter Genes -- III: Preclinical and Clinical Investigations -- Optical Imaging of Primary Tumors -- Nodal Staging of Cancer Using Diagnostic Optical Imaging Techniques -- Optical Coherence Tomography for Cancer Detection -- Optical Imaging of Cancer: Neuro-oncologic Applications.
Keywords: Medicine; Cancer research; Pharmacology; Oncology; Biomedicine; Cancer Research; Oncology; Pharmacology/Toxicology.; Electronic books